2012
DOI: 10.2478/v10183-012-0010-7
|View full text |Cite
|
Sign up to set email alerts
|

Surface and bed morphology of Hansbreen, a tidewater glacier in Spitsbergen

Abstract: Hansbreen, a medium size tidewater glacier in Southern Spitsbergen (Svalbard) is one of the most intensively studied glaciers in the Arctic. This work presents new digital elevation models of its surface and basal topography based on data collected during GPS/GPR campaigns conducted in the spring seasons of 2005 and 2008, as well as on other recent topographic/bathymetric sources. The mean thickness of the glacier is calculated as 171 m and its volume is estimated to be 9.6 (±0.1) km 3 . The main feature of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(88 citation statements)
references
References 35 publications
4
81
3
Order By: Relevance
“…We then performed volume estimates using constant RWVs for the entire glacier, between 165 and 170 m µs −1 , at 1 m µs −1 intervals, and found that the constant RWV that produces the glacier volume closest to that computed using different velocities for distinct media is 166 m µs −1 . This value is within the range of column-averaged RWVs measured on Hansbreen by the authors using the CMP method (Jania et al, 2005;Grabiec et al, 2012). The corresponding volume is 10.75 ± 0.73 km 3 , equivalent, within error bounds, to the volume given above.…”
Section: Radio-wave Velocitysupporting
confidence: 55%
See 3 more Smart Citations
“…We then performed volume estimates using constant RWVs for the entire glacier, between 165 and 170 m µs −1 , at 1 m µs −1 intervals, and found that the constant RWV that produces the glacier volume closest to that computed using different velocities for distinct media is 166 m µs −1 . This value is within the range of column-averaged RWVs measured on Hansbreen by the authors using the CMP method (Jania et al, 2005;Grabiec et al, 2012). The corresponding volume is 10.75 ± 0.73 km 3 , equivalent, within error bounds, to the volume given above.…”
Section: Radio-wave Velocitysupporting
confidence: 55%
“…The volume of Hansbreen presented here is about 1 km 3 (9%) larger than that recently published by Grabiec et al (2012), who used the same set of radar profiles. The main reason is that the outlines of this glacier in the Randolph Glacier Inventory (used here) and in Grabiec et al (2012) differ substantially at the ice divide between Paierlbreen and Hansbreen, implying a difference in the surface area of Hansbreen, which is some 8 km 2 larger in the Randolph Glacier Inventory.…”
Section: Resultscontrasting
confidence: 39%
See 2 more Smart Citations
“…This supposition is supported by the presence of icings in the forefield of glaciers. A similar thermal regime has been reported for other Svalbard glaciers (Jania et # -after www.placenames.npolar.no; $ -without Agnorbreen; * -area in 2015; ** -area in 2014; *** -area in 2010, 1 -total area where icings were observed in the selected years; 2 -area in the years 2008-2015Hodgkins et al 1999;Degard et al 2007;Willis et al 2007;Grabiec et al 2012).…”
Section: Study Area and Methodsmentioning
confidence: 73%